(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
Sheetapitta is a clinical condition caused due to vitiation of Tridosha mainly by the contact of Sheetalavayu. It is characterized by Varati Damstravat Shotha (wheals), Kandu (itching), Daha (burning sensation), Toda (pricking pain), Jwara (fever) and Chardi (vomiting). Sheetapitta analogous to urticaria of western medicine. Urticaria is a vascular reaction pattern characterized by transient, erythematous and edematous wheals or papules of varying sizes and shapes which are usually pruritic. Episodes lasting more than 6 weeks are regarded as chronic urticaria. Present study is a single group open clinical trial with pre and post-test design with a sample size of 33 subjects. The diagnosis was based on the signs and symptoms of Sheetapitta vis-a-vis chronic urticaria and the assessment was based on Urticaria Activity Score which includes wheals and itch as its parameter. Subjects were administered with Virechana Karma followed by Ardraka Khandawith Amruta Rajanyadi Kashaya as Anupana for 30 days after Virechana Karma. The result obtained after the completion of intervention showed statistically highly significant with the P value 0.001 and also overall clinical improvement showed significant result in reducing the signs and symptoms of Sheetapitta vis-a-vis chronic urticaria. Sheetapitta being Tridoshajanya, Virechana Karma helped in Tridosha Nirharana (expelling dosha). Ardraka Khanda being Agnideepaka (appetiser), Sheeta Pittahara (disease pacifying action) and Rasayana (rejuvinator) followed by Amruta Rajanyadi Kashaya which is Kapha-Pitta Hara, Dahahara (reducing burning sensation) and Kanduhara (anti-itch) properties pacified the signs and symptoms of Sheetapitta. In combination of both Virechana Karma and Ardraka Khanda with Amruta- Rajanyadi Kashaya, majority of the subjects attained pacification of urticarial wheals and itching.